Normal range of complement components during pregnancy: A prospective study. (12th November 2019) - He, Ying‐dong; Xu, Bing‐ning; Song, Di; Wang, Ya‐qin; Yu, Feng; Chen, Qian; Zhao, Ming‐hui
Abstract: Problem: The complement system plays a key role in normal placentation, and delicate regulation of complement system activation is critical for successful pregnancy. Therefore, establishing a normal range of complement components during pregnancy is important for clinical evaluation and research. Methods: We performed a prospective study to investigate the normal range of complement components in circulation during different stages of pregnancy. Plasma concentrations of complement factor B (CFB), C1q, complement factor H (CFH), C3, C3c, and C4 were measured using an immunoturbidimetric assay; mannan‐binding lectin (MBL), C3a, C5a, and soluble C5b‐9 (sC5b‐9) levels at different time points of pregnancy were determined by enzyme‐linked immunosorbent assay (ELISA). Results: A total of 733 plasma samples were collected from 362 women with a normal pregnancy and 65 samples from non‐pregnant women. In the first trimester of pregnancy, the levels of CFB, CFH, MBL, C3c, C4, and C3a were 414.5 ± 85.9 mg/L (95% CI for mean: 402.4‐426.6 mg/L), 381.0 ± 89.0 mg/L (95% CI for mean: 368.5‐393.6 mg/L), 4274.5 ± 2752 ng/mL (95% CI for mean: 3881.1‐4656.4 ng/mL), 1346.9 ± 419.8 mg/L (95% CI for mean: 1287.7‐1406.0 mg/L), 357.4 ± 101.8 mg/L (95% CI for mean: 343.0‐371.7 mg/L), and 182.5 ± 150.0 ng/mL (95% CI for mean: 186.9‐229.1 ng/mL), respectively. The levels of C3 and C4 increased gradually throughout pregnancy. The levels of C1q, C5a, and sC5b‐9 in the first and second trimesters were nearly the same as those in non‐pregnant women. Conclusion: The results of this study show that pregnancy itself may influence the plasma levels of complement system components.